Scientific Literature on the Reliability and Validity of the Manchester Triage System (MTS) Protocol: A Integrative Literature Review - Cristiane Chaves de Souza; Francielli Aparecida Araújo; Tânia Couto Machado Chianca (SciELO, 2015)
OBJECTIVE To analyze the scientific production about the validity and reliability of the Manchester Triage System (MTS) protocol. METHOD A descriptive study of an integrative literature review. Articles on the validity and reliability of the MTS developed with children and adults published between 1999 and 2013 were included. RESULTS 14 articles were selected from a total of 8438, nine of validity and five of reliability. The reliability of the MTS ranged from moderate to almost perfect, with higher intra-evaluation. Regarding validity, the results seem to point to equivalent and satisfactory sensibility and specificity levels of the MTS. The instrument proved to be a good predictor of the need for hospitalization and of hospital mortality. CONCLUSION The reliability and validity of the MTS obtained in the studies is varied. It is recommended that new studies indicate necessary modifications to the MTS so that it is more safely used by nurses.